Synthesis, Spectral and Thermal Studies of Some Divalent Metal Complexes with 8-Acetyl-7-Hydroxy-4-Methyl Coumarin Oxime/Hydrazone†. - POKHARIYAL, G.P.; LAL, BABU; RASTOGl, V.K. (Asian Journal of Chemistry, 2010)
In the present work some divalent transition metal complexes of biologically active ligands are synthesised and characterised.